Pengembangan Alat Uji Efisiensi Lampu Berbasis Mikrokontroller Arduino Uno untuk Evaluasi Tingkat Pencahayaan Lampu Meja Belajar di Laboratorium Fisika-Mekatronika Politeknik STTT Bandung - Putra, Valentinus Galih Vidia; Wijayono, Andrian; Ngadiyono, Ngadiyono; Purnomosari, Endah (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2020)
In this research, a light efficiency test tool has been designed using an Arduino UNO microcontroller to provide an understanding of the use of the ohm law application in basic physics practicum. This lamp efficiency test prototype uses an LDR sensor device and a resistor connected to the Arduino microcontroller as a light intensity detector, while the variation of electrical power is used by an AC variac with the lamp distance to the sensor having a constant value. The experimental results showed that the efficiency of the lamp can be obtained through a gradient of the luminosity curve on electric power. The efficiency of the lamp is 16.935 lm/watt and the average resistance can be obtained on 983.01 which the intensity in lux is 337,05 lux on 157,68 Lm and the maximum intensity in lux can be obtained on 453,35 lux on 208,54 Lm.